Biomass gasification using mixtures of air, saturated steam, and oxygen in a two-stage downdraft gasifier. Assessment using a CFD modeling approach. (November 2021) - Yepes Maya, Diego Mauricio; Silva Lora, Electo Eduardo; Andrade, Rubenildo Vieira; Ratner, Albert; Martínez Angel, Juan Daniel
Abstract: This work proposes and employs a mixed-complexity modeling approach to creating a 3D computational fluid dynamics (CFD) model to predict the syngas production from Miscanthus briquettes in a two-stage downdraft gasifier operating with different gasification fluids. The study was performed at steady state regime in the Ansys Fluent environment considering the non-premixed combustion model. A probability density function is also included as a tool for the description of the chemical kinetics to predict the syngas composition following the main chemical reactions involved in the gasification process. The goal of this approach is to reduce the computational cost while still providing accurate predictions. In comparison to experimental gasification with air, the model correctly predicts the temperature profile inside the reactor, the composition of the syngas (CO, H2 and CH4 ), and therefore the lower heating value (LHV). For cases involving the use of saturated steam and oxygen as gasification fluids, the model predicted key species concentrations in the gasification zone and the reactor core and accurately described the significant increase in the LHV of the syngas. This approach opens the possibility of studying the gasification process in moving-bed reactors using different gasification fluids and feedstocks based on their elemental and proximate analysis. Highlights: The non-premixed model and the probability density function were used. Miscanthus briquettes were studied by using a double-stage downdraft gasifier. The use of air, saturated steam, oxygen, and their combinations as gasification agents. The application of the CFD model to a two-stage downdraft gasifier. CFD modeling results and experimental data are in good agreement.